The Application of Learner-Guided Study to Improve Students’ Analytical exposition Writing Skills in EFL Classroom - Syaadiah Maula Arifin; Hamzah Puadi Ilyas (Universitas Pendidikan Ganesha, 2022)
The learner guided study is innovative learning activity planned by a group of teachers considered better than those made by the individual teacher. However, its effectiveness in retaining the students learning is still dubious since there is no apparent connection between students' learning variety and needs. The aim of this study is to analyze the effectiveness of the learner-guided study in improving students’ analytical exposition writing competence. The participants were thirty high school students in grade eleventh. They often encountered difficulties in mastering analytical exposition due to the lack of specific practices. The data analysis was carried out using a mixed-method design. They were gathered from the analytical exposition writing tests and interviews. The results from this study demonstrated that the Experimental group taught with a guided lesson study surpassed the Control Group taught by the unguided lesson study. The guided lesson helped students achieve the learning goals of the analytical exposition aspects. This study recommends that this procedure be used to teach writing in any genre, as it could improve the students’ writing skills.